2006
DOI: 10.1002/ffj.1716
|View full text |Cite
|
Sign up to set email alerts
|

The essential oil composition of devil's club, Oplopanax horridus J. E. Smith Miq.

Abstract: Devil's club has been used in folk medicine by the native tribes of Alaska and British Columbia for centuries for the treatment of colds, fever, burns, stomach troubles and even tuberculosis. 4,5 ExperimentalStems and roots of O. horridus were collected from the same plant stands on 30 December 2002 near Chilliwack, British Columbia, Canada, at about 200 -300 m altitude. A voucher specimen (no. V219467) was deposited at the Herbarium of the University of British Columbia, Vancouver, Canada. Both oils, the one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…It was observed that the main constituent in both the stem and root essential oils was nerolidol with over 50% of the oil being composed of this compound, a finding corroborated by a number of studies [19, 23, 24]. Another study examined the volatile oil from the leaves of OH, and the results showed that 2-methyl-6-p-methylbenzene-2-heptene (34.4%) and phytol (8.13%) are the main constituents among a chromatogram with forty-five peaks [25].…”
Section: Chemical Studiessupporting
confidence: 55%
“…It was observed that the main constituent in both the stem and root essential oils was nerolidol with over 50% of the oil being composed of this compound, a finding corroborated by a number of studies [19, 23, 24]. Another study examined the volatile oil from the leaves of OH, and the results showed that 2-methyl-6-p-methylbenzene-2-heptene (34.4%) and phytol (8.13%) are the main constituents among a chromatogram with forty-five peaks [25].…”
Section: Chemical Studiessupporting
confidence: 55%
“…Five polyynes were isolated from O. horridus : falcarinol; falcarindiol; oplopandiol; oplopandiol acetate; 9,17-octadecadiene-12,14-diyne-1,11,16-triol 1-acetate [9]. Based on GC/MS techniques, the composition of the essential oil of devil’s club was studied, and (E)-nerolidol was found to be the major constituent in both the stems (54.5%) and the roots (54.6%) [36]. …”
Section: Discussionmentioning
confidence: 99%
“…However, comparison with the chromatographic profile presented is difficult because of instrumentation, column, and mobile phase differences. In addition, Garneau et al (2006) identified a number of essential oils in both the stem and root and found that nerolidol comprised more than 50% of both extracts. In our chromatographic profile the peak at 39.5 min was confirmed as nerolidol by both retention time and mass spectral information using liquid chromatography-mass spectrometry.…”
Section: Discussionmentioning
confidence: 98%